Impact of Humic Acid Levels on Yield Attributes of Sugarcane Chip Bud Settlings in District Mardan - Beena Saeed; Anam Sadiq (Kurdish Studies, 2023)
The research was carried out at Sugar Crops Research Institute (SCRI) Mardan, Pakistan during 2013. The experiment was placed out in randomized complete block design (RCBD) with three replications. Chip bud settlings of sugarcane variety CP-1827 was transplanted in March 2014, within a plot size 10 m by 6.7m (67m2) with 90 cm row to row distance and 60 cm plant to plant distance. Four levels of humic acid i.e control: 9.88: 14.82 and 19.76 kg ha-1 were compared during the study. The results investigated significant effects of different levels of humic acid upon all parameters except plant height and quality parameters like pol (%), brix (%) and sugar recovery was not significantly influenced by different levels of humic acid. While number of tillers m-2, number of internodes length per tiller, stem diameter, internodes length, and cane yield had significantly influenced by different levels of humic acid specifically where humic acid was applied at the rate 19.76 kgha-1. It was determined that the use of humic acid at the proportion of 19.76 kg ha-1 enhanced the number of internodes, stem diameter, and cane yield as compared with other levels of humic acid and hence recommended for obtaining higher cane yield from chip bud settling of sugarcane in agro ecological condition of Peshawar valley.